The Influence of Service Quality and Price on Customer Satisfaction at the Putri Minang Restaurant, Sukadana Ilir Village, East Lampung Regency - Muhamad Nasihin; Denny Kurniawan; Robi Santoso; Dina Nadiyah Faiqoh (Indonesian Journal of Entrepreneurship and Startups, 2026)
Tight competition in the culinary industry requires business actors to make customer satisfaction a top priority in business sustainability. Customer satisfaction is influenced by various factors, including the quality of service and price offered. Based on this explanation, this study focuses on examining the impact of service quality and price on customer satisfaction at Putri Minang Restaurant, Sukadana Ilir Village, East Lampung, both partially and simultaneously. The approach applied in this study is a quantitative descriptive approach, with data collection instruments that include observation, documentation, and distribution of Likert-based questionnaires to collect primary and secondary data. Data processing is carried out through multiple linear regression analysis techniques using statistical software. Based on the results of the analysis, the regression equation Y = 20.674 + 0.322 X1 + 0.426 X2 + e is obtained, which indicates a positive correlation between the variables of service quality and price on customer satisfaction. Furthermore, partial testing (t-test) shows a significance value for service quality (X1) of 0.002 and price (X2) of 0.000. Both obtained values ​​below 0.05. This proves that each variable has a partial and significant effect on customer satisfaction. This finding is reinforced by a simultaneous test (F-test) with a significance level of 0.000 < 0.05, which shows that service quality and price together have a significant impact on customer satisfaction. The level of influence of the independent variable on the dependent variable is seen from the coefficient of determination (R²) value which shows the number 0.619, which means that service quality and price affect customer satisfaction by 61.9%. Meanwhile, 38.1% is influenced by other variables that have not been explained in this research model